Economic evaluation of Australian acute care accreditation (ACCREDIT-CBA (Acute)): study protocol for a mixed-method research project. Issue 2 (8th February 2013) - Mumford, Virginia; Greenfield, David; Hinchcliff, Reece; Moldovan, Max; Forde, Kevin; Westbrook, Johanna I; Braithwaite, Jeffrey
Abstract : Introduction: The Accreditation Collaborative for the Conduct of Research, Evaluation and Designated Investigations through Teamwork—Cost–Benefit Analysis (ACCREDIT-CBA (Acute)) study is designed to determine and make explicit the costs and benefits of Australian acute care accreditation and to determine the effectiveness of acute care accreditation in improving patient safety and quality of care. The cost–benefit analysis framework will be provided in the form of an interactive model for industry partners, health regulators and policy makers, accreditation agencies and acute care service providers. Methods and design: The study will use a mixed-method approach to identify, quantify and monetise the costs and benefits of accreditation. Surveys, expert panels, focus groups, interviews and primary and secondary data analysis will be used in cross-sectional and case study designs. Ethics and dissemination: The University of New South Wales Human Research Ethics Committee has approved this project (approval number HREC 10274). The results of the study will be reported via peer-reviewed publications, conferences and seminar resentations and will form part of a doctoral thesis.